High flow nasal cannula use outside of the ICU; factors associated with failure - Betters, Kristina A.; Gillespie, Scott E.; Miller, Judson; Kotzbauer, David; Hebbar, Kiran B. (Pediatric pulmonology, 2017)
Summary Objectives High flow nasal cannula (HFNC) use is increasing in pediatrics. Few studies exist examining the safety of HFNC use outside the intensive care unit (ICU). This study aimed to characterize patient qualities associated with failure of HFNC use outside the ICU. Study Design A retrospective chart review of patients placed on HFNC outside the ICU from September 2011 to July 2013 was completed. Failure was defined as intubation or cardiopulmonary arrest. Two‐sample tests and binary logistic regression determined significant factors associated with failed HFNC administration, both unadjusted and adjusted for hospital. Results Two hundred thirty‐one patients met inclusion criteria, with 192 receiving treatment for a primary respiratory diagnosis (83%). Fourteen (6%) progressed to HFNC failure; 12 transferred to the ICU and were intubated, two with congenital heart disease suffered cardiopulmonary arrest on the floor. Two‐sample tests revealed failure patients were more likely to have a cardiac history (P = 0.026), history of intubation (P = 0.040), and require higher fraction of inspired oxygen (FiO2) (median 100%; 25th–75th 60–100%; P = <0.001). Hospital adjusted logistic regression further demonstrated failure patients were more likely to be treated with higher FiO2 (OR: 38.3; 95% CI: 4.0–366.3; P = 0.002), and less likely to have a diagnosis of bronchiolitis (OR: 0.3; 95% CI: 0.1–0.9; P = 0.048). Conclusions High FiO2 requirements, history of intubation, and cardiac co‐morbidity are associative predictors of HFNC failure. Bronchiolitis patients may be treated with HFNC outside of the ICU with lower odds of failure. Pediatr Pulmonol. 2017;52:806–812. © 2017 Wiley Periodicals, Inc.